CRISPR/Cas9-editing of KISS1 to generate pigs with hypogonadotropic hypogonadism as a castration free trait - Flórez, Julio M.; Martins, Kyra; Solin, Staci; Bostrom, Jonathan R.; Rodríguez-Villamil, Paula; Ongaratto, Felipe; Larson, Sabreena A.; Ganbaatar, Uyanga; Coutts, Alexander W.; Kern, Doug; Murphy, Thomas W.; Kim, Eui-Soo; et al. (Frontiers in Genetics, 2023)
Most male pigs are surgically castrated to avoid puberty-derived boar taint and aggressiveness. However, this surgical intervention represents a welfare concern in swine production. Disrupting porcine KISS1 is hypothesized to delay or abolish puberty by inducing variable hypogonadotropism and thus preventing the need for castration. To test this hypothesis, we generated the first KISS1-edited large animal using CRISPR/Cas9-ribonucleoproteins and single-stranded donor oligonucleotides. The targeted region preceded the sequence encoding a conserved core motif of kisspeptin. Genome editors were intracytoplasmically injected into 684 swine zygotes and transferred to 19 hormonally synchronized surrogate sows. In nine litters, 49 American Yorkshire and 20 Duroc liveborn piglets were naturally farrowed. Thirty-five of these pigs bore KISS1-disruptive alleles ranging in frequency from 5% to 97% and did not phenotypically differ from their wild-type counterparts. In contrast, four KISS1-edited pigs (two boars and two gilts) with disruptive allele frequencies of 96% and 100% demonstrated full hypogonadotropism, infantile reproductive tracts, and failed to reach sexual maturity. Change in body weight during development was unaffected by editing KISS1. Founder pigs partially carrying KISS1-disruptive alleles were bred resulting in a total of 53 KISS1+/+, 60 KISS1+/−, and 34 KISS1−/− F1 liveborn piglets, confirming germline transmission. Results demonstrate that a high proportion of KISS1 alleles in pigs must be disrupted before variation in gonadotropin secretion is observed, suggesting that even a small amount of kisspeptin ligand is sufficient to confer proper sexual development and puberty in pigs. Follow-on studies will evaluate fertility restoration in KISS1 KO breeding stock to fully realize the potential of KISS1 gene edits to eliminate the need for surgical castration.